General decay of solutions to a viscoelastic wave equation with linear damping, nonlinear damping and source term. Issue 7 (18th May 2020) - Li, Qian; He, Luofei
ABSTRACT: This paper is concerned with the decay property of a nonlinear viscoelastic wave equation with linear damping, nonlinear damping and source term. Under weaker assumption on the relaxation function, we establish a general decay result, which extends the result obtained in Messaoudi [Exponential decay of solutions of a nonlinearly damped wave equation. Nodea-Nonlinear Differ Equat Appl. 2005;12:391–399].